KONFLIK PEDAGANG DENGAN PT. SANUR DINAMIKA MENTARI: STUDI KASUS PENGELOLAAN LAHAN PEMBANGUNAN HOTEL DI PANTAI MERTASARI SANUR - Darma Kusuma, Wahyu (JURNAL ILMIAH SOSIOLOGI (SOROT), 2012)
Basically this research would like to know about the form of conflict which been happened at Mertasari Sanur lately that become a very main topic between the Street TradersÂ and PT. SDM. The explanation then will be followed by looking how are the effects would be appears when the conflicts happened. Whereas the purpose of this research is to explore and effort the problem solving without disadvantaging the both party. Whereas the type of research will be was is Qualitative Research. This method is used to understand the conflicts based on this research at the area. This research is descriptive analytic which means by describing and explaining indication, incident, phenomenon, and something has happened. Researchâ€™s result shows that the type of conflict between the Street traders and PT. SDMÂ is type of Structural Conflict.